The Influence of Financial Literacy and Financial Digitalization on the Profitability: Study on Micro and Small Enterprises Business Incubator in Palu City, Indonesia - Sitriani, Afifah; Zainuddin, Fatlina; Muslimin, M.; Risendy, Rian (Manunggal Halim Jaya, 2025)
This study aims to analyze the effect of financial literacy and financial digitalization on the profitability of MSMEs registered with the Palu City Business Incubator (INBIS) in the 2023-2024 period. Given the crucial role of MSMEs in the local economy and the challenges related to financial literacy and digitalization adoption, this study seeks to provide empirical evidence. A quantitative approach with descriptive and causal methods was used, involving 30 MSMEs through a census to obtain comprehensive data. Data analysis was carried out using multiple linear regression. The results showed that financial literacy significantly affected MSME profitability, making a greater contribution than financial digitalization. Financial digitalization also had a positive impact, although its contribution was relatively smaller. Simultaneously, financial literacy and financial digitalization significantly affected MSME profitability. These findings emphasize the importance of a combination of good financial literacy and adoption of digital technology. The implication is that the government and INBIS need to design a sustainable integrated training program to improve MSME digital financial literacy. MSMEs are advised to actively utilize digital financial platforms and improve their understanding of financial management. Financial institutions are expected to develop products according to MSME needs and provide more effective financial education. This research provides insights for stakeholders in supporting the growth of MSMEs through increasing literacy and digital transformation, which ultimately contributes to regional economic stability.